2021
DOI: 10.1097/yct.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Comparison of Perceptions and Knowledge About Electroconvulsive Therapy Among Adults Who Screened Positive for Depression in the United States, India, and China

Abstract: Objective: Despite the established efficacy of electroconvulsive therapy (ECT), negative perceptions and inaccurate knowledge about ECT in the United States and other countries persist. This study examined ECT perceptions and knowledge in the 3 most populous countries in the world. Methods:We recruited participants who screened positive for depression on the Patient Health Questionnaire 9 (PHQ-9) in the United States (n = 1643), India (n = 1469), and China (n = 328) and compared responses on the ECT-Perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For example, a recent study found that both older Chinese patients with severe psychiatric disorders and their caregivers mostly reported positive attitudes towards ECT (19). The possible reasons for the above inconsistent findings were mainly attributed to the fact that the use of ECT is associated with cultural, social, and legal factors (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study found that both older Chinese patients with severe psychiatric disorders and their caregivers mostly reported positive attitudes towards ECT (19). The possible reasons for the above inconsistent findings were mainly attributed to the fact that the use of ECT is associated with cultural, social, and legal factors (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found that more adolescents with psychiatric disorders (55.7%) reported receiving adequate information about the therapeutic effects of ECT than their caregivers (50.6%) (20). Given that ECT practice is influenced by cultural, social, and legal factors, findings from previous studies on ECT attitudes and knowledge from other countries or regions may not be applicable to samples in different regions of China (22)(23)(24).…”
Section: Introductionmentioning
confidence: 94%
“…Some work suggests that people who lack specific knowledge of newer PEI interventions may rely on general attitudes toward more well-known PEIs (like ECT), which are largely negative 8 . In the absence of reliable information, negative attitudes toward PEIs proliferate and influence perceptions of these treatments’ efficacy, safety, and side effects 1 , 8 , 21 , 25 .…”
Section: Introductionmentioning
confidence: 99%